Electrochemical Kinetics of Anodic Ni Dissolution in Aqueous Media as a Function of Chloride Ion Concentration at Ph Values Close to Physiological Conditions - Zagal-Moya, J; Zagal-Moya, J (2012)
We have studied the electrochemical kinetics of anodic Ni dissolution as a function of chloride ion concentration, at pH5, 6 and 7, in order to mimic the conditions of sweat samples. Our results show that the rate-determining step for Ni dissolution in the mentioned pH range is the transfer of one first electron, as suggested by the Tafel slopes close to 0.120V/decade. However, the reaction order in chloride ion varies from ca. 2 at pH7 to values close to unity for pH values between 5 and 6. This finding is very important for sensor applications in sweat fluids since the sensitivity of the Ni electrode to chloride ions is higher in neutral solutions (pH ca. 7) compared to that in slightly acid solutions (pH between 5 and 6). Small variations in pH in real samples are expected so this change in sensitivity should be considered when sensing chloride ions in sweat fluids. © 2012 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.